Transparansi Anggaran dan Kesadaran Pajak Terhadap Kepatuhan Pajak - Islami, Putri Madania; Askandar, Noor Shodiq; Fakhriyyah, Dewi Diah (Universitas Islam Malang, 2024)
Tax compliance is a condition where taxpayers fulfill their tax obligations according to applicable regulations. The purpose of this research is to determine and explain the influence of budget transparency and tax awareness on tax compliance. The research methodology used is quantitative, employing numerical data. The population studied consists of individual taxpayers registered at the North Malang Primary Tax Office. The sample in this study was selected using Accidental Sampling, with a sample size of 100 respondents determined using Slovin's formula. The research utilizes primary data analysis and multiple linear regression, with hypothesis testing conducted using SPSS Version 29. The results of the study indicate that budget transparency and tax awareness have a significant and positive influence on tax compliance. This research supports the attribution theory and the Theory of Planned Behavior (TPB).Keywords: budget transparency, tax awareness, tax compliance.